Delays On Distribution Of Inheritance As Wise As From The Perspective Of Positive Law And Fiqh Law According To Ulama In Aceh - Lukmanul Hakim (LAWYER: Jurnal Hukum, 2023)
This research describes the delay in distribution of inheritance according to positive law and fiqh law according to ulama in aceh. the purpose of this research is education and advocacy for the community. according to postive law and fiqh law, inheritance is an absolute right of the heirs which should be distributed immediately after paying off the debts and inheritance of the heirs, but because the distribution is not hastened, it has a negative impact on the heirs. delays in dividing inherited assets result in loss of rights and changes in the value of inherited assets. this phenomenon often occurs in society in general, especially the people of aceh tamiang regency. this type of research is field research where the main source is the results of field interviews. The results of this research based on the perspective of positive law and fiqh law are: 1) the impact of delays in the distribution of inheritance, namely: the occurrence of family problems/breakdown of ties between heirs, which can result in loss of property value, as well as abuse of some heirs because of their rights. not fulfilled. 2) the views of the aceh tamiang ulama regarding postponing the distribution of inheritance are divided into three laws, namely: obligatory postponement, permissible postponement, and haram postponement. these three laws are adapted to the situation that occurs if the distribution of inheritance is delayed due to doubts regarding the lineage and/or doubts about whether or not heirs are obligated for life until there is a determination of the lineage and/or heirs from the court. likewise, delaying the distribution of inheritance due to doubts due to the actual pregnancy or doubts regarding gender (khunsa) is mandatory so that the status of both is clear. if you postpone the distribution of inheritance, if you get the approval of all the rightful heirs and are mu'tabar in giving permission and administering it according to sharia law, then it is permissible. if delaying the distribution of inherited assets creates injustice for the heirs or results in losses and a decrease in the value of the assets, then the law is haram.